Pengaruh Dewan Komisaris dan Corporate Social Responsibility terhadap Financial Performance Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Ryan Zulhariyahya; Cahyadi Husadha; Elia Rossa (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The implementation of the Board of Commissioners and Corporate Social Responsibility is important for a company. By implementing the Board of Commissioners and Corporate Social Responsibility properly and correctly, it will improve the image of the company, this will also improve the company's Financial Performance. This research aims to determine the influence of the Board of Commissioners and Corporate Social Responsibility variables on Financial Performance in banks listed on the IDX. The sampling technique in this research used purposive sampling which produced 29 samples over 4 years, namely 116 samples. The analytical method used is multiple regression analysis which is processed using Eviews Version 12. The research results show that only the Board of Commissioners has an influence on Financial Performance. while Corporate Social Responsibility has no effect on Financial Performance. Meanwhile, the results of the Board of Commissioners and Corporate Social Responsibility simultaneously have effect on Financial Performance.